Causal Loop Diagram Kepuasan Pelanggan terhadap Layanan Publik: Studi Kasus Direktorat Registrasi Pangan Olahan, BPOM - Rahajeng Puput Aryani (Eruditio : Indonesia Journal of Food and Drug Safety, 2022)
One of the performance indicators used by the Directorate of Processed Food Registration is the customer satisfaction survey. The majority of performance metrics rose in 2020, but the customer satisfaction survey results in Directorate of Processed Food Registration actually fell from 83.96 in 2019 to 82.60 in 2020. This study aims to understand the structure of customer satisfaction with public services at the Directorate of Processed Food Registration. Causal Loop Diagrams (CLD) are used to represent the problems arising, key variables, feedback between variables, and recommended variables for intervention. A literature review, customer satisfaction survey results analysis, and Focus Group Discussions (FGD) with managers and all teams in public service are used to identify the variables. According to the CLD results, the workload variable is the key variable that influences customer satisfaction. Customer satisfaction and the variables of willingness and awareness in the registration process are mutually reinforcing. On the other hand, a rise in registration applications could lead to customer complaints since officers' workloads would increase beyond their ability and the officers wouldn't have opportunities to advance their skills. The constructed customer satisfaction structure can be used to choose the variables to be intervened. The intervention variables are: registration socialization, non-evaluation registration, officer, and reward. The well-mapped socialization program can increase customer awareness of the registration requirement. As a result of the intervention, there are increased registration requests and officer workloads. Furthermore, to respond to the increase in registration requests, non-evaluation and increasing the number of officers might be used. In addition, intervention in the form of reward also could contribute as a motivation for officers to enhance their performance. The intervention of these variables can be used for a series of ongoing processes and can be used to support leaders in making decisions.